ANALISIS KECERDASAN EMOSIONAL GURU DITINJAU DARI MOTIVASI BELAJAR SISWA SMK MUHAMMADIYAH MEGANG SAKTI KABUPATEN MUSI RAWAS - Astuti Karya Dewi; Shoriyani Shoriyani (Jurnal Media Ekonomi (JURMEK), 2017)
This study aims to determine the emotional intelligence of teachers in terms of student learning motivation. The theory used is Human Resources related to Emotional Intelligence in terms of student learning motivation. The method used in this research is observation, interviews, and documentation, this type of research is qualitative analysis and the nature of this research is descriptive (illustrated). The data source used in this study is primary, which is about interviews with regard to research. The number of samples used purposive sampling technique consisting of 4 samples. Data analysis model used through structured interviews to participants. The conclusion of this study is the analysis of teacher emotional intelligence is quite good at the Muhammadiyah Megang Sakti Vocational School, Musi Rawas district. Emotional Intelligence, Motivation